PENGELOLAAN LAYANAN PENGADUAN MASYARAKAT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MANADO - Rahmawaty Wumu; JOHNNY HANNY POSUMAH; NOVVA NOVITA PLANGITEN (JURNAL ADMINISTRASI PUBLIK, 2023)
ABSTRACT This study aimed to determine the management of the public complaints services in the city of manado and civil registry service. Research conducted is a descriptive study using qualitative data. The management of the complaints services was observed with the four functions of management: planning, organization, movement and supervision. As for the data sources that researchers have gathered in this study come from two types of data, secondary (acquired directly) and primary data (acquired indirectly). The informers in this study are the chief of the ministry, the chief of the complaint, the service secretary, and the public service service service, the total number of 8 informers. Data collection is done with interviews and observations, interactive model analysis techniques by miles and hubermans are used in the study. The results of this study drew the conclusion that the existing public complaint services still did not meet standards in their management because the resources in this complaint service were still inadequate and management targets had not been achieved. Researcher suggestionsIn managing complaint services at this agency, it is hoped that more attention can be paid, where resources and infrastructure are still lacking and need to be improved again.  Key words : Management, Public Grievance Services.